Feasibility study phase 2: Klinik Dr. Rosli Klinik Kanak-Kanak dan Dewasa Section 18, 40000 Shah Alam Selangor Darul Ehsan / Gluma Saban...[et al.] - Saban, Gluma; Mohsin Bledrom, Abd Rahman; Azhar, Aznor; Ramli, Azizi; Idris, Mohd Ezani; Ibrahim, Shamsol Anuar (1990)
This report is compiled in partial fulfillment of the requirement of Management Information System (MIS) subject. This report is based on t h e automation of the patients registration process in Dr. Rosli's Clinic . The objectives to implement this system are to define procedure clearly, to simplify and improve paperwork processing efficiently, to improve accurate record keeping, and to implement an online medical system.